Search for CP violation in D+ (s) → h+π0 and D+ (s) → h+η decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2021)
Searches for CP violation in the two-body decays D+ (s) → h+π0 and D+ (s) → h+η (where h+ denotes a π+ or K+ meson) are performed using pp collision data collected by the LHCb experiment corresponding to either 9 fb−1 or 6 fb−1 of integrated luminosity.